STUDI KOMPARATIF OMNIBUS LAW PERSEROAN TERBATAS MENURUT UNDANG-UNDANG NOMOR 40 TAHUN 2007 DENGAN PERSEROAN PERORANGAN - Yusuf, Helmi (Qonuni: Jurnal Hukum dan Pengkajian Islam, 2022)
The purpose of this study is to analyze the comparison of limited liability companies according to law number 40 of 2007 and law number 11 of 2020 concerning Job Creation using normative juridical research methods. This study found that there are differences between PT according to Law number 40 of 2007 and the Job Creation Law in terms of definition, status, establishment of a Limited Liability Company, Directors, Commissioners, Capital, Company Organs, Business Expansion, Establishment of PT, Ministerial Decree, Changes in Financial Statements and Dissolution.